The whole organization system management mode in the treatment of COVID-19 - Zhenhua Yang; Xiaobo Ma; Xiaobo Ma; Weiyi Zhu; Weiyi Zhu (Frontiers in Public Health)
BackgroundDuring the epidemic period, the designated hospital model is very effective in blocking the spread of diseases. A suitable management mode helps to carry out work better.ObjectiveThis study was aimed to explore and practice the management mode on the epidemic situation of COVID-19 disease in the designated hospital.MethodsThe study involved the establishment of the whole organization system management mode in the treatment of COVID-19 through standardized nursing staff allocation and management, infection control protocols, and the implementation of nursing practices under a comprehensive organizational management framework and apply it in the medical wards of the designated hospital. The patients were uniformly admitted to our ward.FindingsThe use of the whole organization system management mode ensured the ordered, stable, and high-efficient medical treatment of COVID-19 patients in the medical wards of the designated hospitals. During the 71 days medical treatment, 880 cases of COVID-19 patients were treated, that included 48 cases of patients with complex conditions and elder patients with severe illnesses and 846 cases of discharged patients. There were no death cases of critically ill patients in the above cases and no nosocomial infection of the staff in the medical treatment of COVID-19.ConclusionThe whole-organization management mode is conducive to the ordered, stable, and efficient promotion in the wards of the designated hospitals for COVID-19 and can provide a reference to take over medical wards work for all kinds of medical tasks.